(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This study critiques two prevailing epistemological tendencies in the study of vernacular architecture in Indonesia: The universalism of form, which relies on Western formal theories, and cultural relativism, which romanticizes the uniqueness of local traditions. Both tendencies are considered to offer limited contributions to the vernacular communities under study, as they often result merely in formal descriptions or cultural idealizations without addressing the transformative potential of architectural design. This study aims to formulate a new interpretive tool for identifying the local values of Indonesian vernacular architecture while simultaneously exploring its transformative potential. The study employs a three-step analytical phases: Firstly, tracing the development of theoretical studies on vernacular architecture in Indonesia to map their epistemological limitations. Secondly, elaborating the theory of architectural ethnosemantic with the concept of architectural property–composition, in order to generate an analytical framework that bridges formal and semantic aspects. Thirdly, applying the results of this elaboration to identify local values and transformative potential in vernacular settlements in Indonesia. The focus of inquiry is directed toward Sundanese villages in West Java that have already undergone transformations, taken as a representation of the vernacular traditions of the Indonesian archipelago. The findings of this study are an interpretive model for examining the local values of Sundanese architecture, together with the potential transformations in housing and settlement design. This formulation serves a dual function: as an academic contribution to the advancement of vernacular theory, and as a practical contribution to improving the quality of life of the vernacular communities themselves.